Vulcanized rubber and preparation method thereof
By using the combination of denitrification white latex with amino acid functional additives and vulcanization accelerators in natural rubber, vulcanization treatment is solved, and high stretching and anti-aging properties are achieved Improvement.
Patent Information
- Application Number
- CN202411514110.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Protein allergic reaction problems present in natural rubber latex lead to allergic reactions, and the tensile and anti-aging properties of deproteined natural latex are poor.
The natural latex of nitrogen removal is combined with functional additives such as serine, arginine, and lysine. The vulcanization treatment is carried out through the use of vulcanization accelerators such as N-tert-butyl-2-benzothiazolesulfonamide, etc., and the vulcanization treatment is carried out to form Vulcanized rubber improves its tensile properties and anti-aging properties.
It significantly improves the tensile and anti-aging properties of vulcanized rubber, reduces network defects, enhances the utilization rate of zinc oxide and sulfur, improves the construction of rubber matrix network, and improves the comprehensive performance of the material.
Smart Images

Figure CN119241926A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber, and in particular to a vulcanized rubber and a preparation method thereof. Background Art
[0002] Natural rubber latex is an ideal material for expandable elastic products such as medical appliances, catheters, tapes, tourniquets, gloves and condoms due to its green biological source, excellent membrane strength, high elasticity and memory. However, natural rubber latex contains latex protein that causes skin allergy, and the allergic reaction caused by protein in latex is the biggest problem faced by medical natural rubber latex products. Studies have found that among most people who often come into contact with natural rubber latex and its products, the number of allergic patients has reached epidemic levels. These individuals experience allergic reactions such as rhinitis, conjunctivitis, contact urticaria, bronchial asthma, and even sudden death when they come into contact with the products. At present, the available way to circumvent natural rubber latex protein allergy is to remove the protein in natural rubber latex, that is, deproteinized natural latex. However, deproteinized natural latex currently has the problem of poor tensile properties and anti-aging properties. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present invention provides a vulcanized rubber and a preparation method thereof. The vulcanized rubber provided by the present invention has good tensile properties and anti-aging properties.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a vulcanized rubber, wherein the raw materials for preparing the vulcanized rubber include, by weight:
[0006]
[0007] The nitrogen content of the denitrogenated white natural rubber latex is 0.02 to 0.2 wt.%;
[0008] The functional auxiliary agent includes one or more of serine, arginine, lysine and glutamic acid.
[0009] Preferably, the vulcanization accelerator includes one or more of N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole and dibenzothiazole disulfide.
[0010] Preferably, the preparation of the deproteinized natural rubber latex comprises the following steps:
[0011] (1) mixing natural rubber latex, urea and a stabilizer, and sequentially standing and centrifuging the resulting mixed solution to obtain a pretreated natural rubber latex;
[0012] (2) diluting the pretreated natural rubber latex, mixing the obtained dilution with ammonia water and a stabilizer, and centrifuging again to obtain deproteinized natural rubber latex.
[0013] Preferably, the stabilizer is one or more of sodium dodecyl sulfate, sodium petroleum sulfonate, Tween and PEG.
[0014] Preferably, in step (2), the aqueous ammonia accounts for 0.3-0.7% of the mass of the diluent.
[0015] Preferably, in step (2), the stabilizer is 0.2-0.6% of the mass of the diluent.
[0016] The present invention also provides a method for preparing the vulcanized rubber described in the above technical solution, comprising the following steps:
[0017] Mixing deproteinized natural rubber latex and functional additives to obtain modified deproteinized natural rubber latex;
[0018] The modified deproteinized natural rubber latex, the emulsion of the vulcanization accelerator, the emulsion of sulfur and the emulsion of zinc oxide are mixed, and the obtained mixture is molded and dried to obtain a mixed dry rubber;
[0019] The mixed dry rubber is kneaded and vulcanized in sequence to obtain the vulcanized rubber.
[0020] Preferably, the mixing method is stirring; the stirring speed is 100 to 1000 rpm, and the stirring time is 10 to 60 min.
[0021] Preferably, the mixing is to mix the mixed dry rubber at 40-70° C. for 20-60 times using a mixing roller.
[0022] Preferably, the vulcanization temperature is 140-180° C., the vulcanization pressure is 8-20 MPa, and the vulcanization time is 10-50 min.
[0023] The present invention provides a vulcanized rubber, wherein the raw materials for preparation include, by weight: 100 parts of deproteinized natural latex; 2.5 to 20 parts of vulcanization accelerator; 0.05 to 5 parts of functional additives; 0.2 to 3 parts of sulfur; 2 to 7 parts of zinc oxide; the nitrogen content of the denitrified white natural latex is 0.02 to 0.2 wt.%; the functional additives include one or more of serine, arginine, lysine and glutamic acid. The functional additives in the vulcanized rubber provided by the present invention help promote the formation of complexes by Zn ions, promote the dispersion and solubility of the complexes in the rubber matrix, and the formed amine-containing complexes can promote the ring opening and activation of sulfur elements, thereby improving the utilization of zinc oxide and sulfur, promoting the construction of the rubber matrix network, and reducing network defects, thereby improving the tensile properties and aging properties of the deproteinized natural latex. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The C, N, S, and Zn analysis elements of deproteinized vulcanized natural rubber UFNR under scanning electron microscopy and corresponding X-ray spectrum;
[0025] Figure 2 The C, N, S, and Zn analysis elements of A-0.9 vulcanized natural rubber under scanning electron microscopy and corresponding X-ray energy spectrum. DETAILED DESCRIPTION
[0026] The present invention provides a vulcanized rubber, wherein the raw materials for preparing the vulcanized rubber include, by weight:
[0027]
[0028] The nitrogen content of the denitrogenated white natural rubber latex is 0.02 to 0.2 wt.%;
[0029] The functional auxiliary agent includes one or more of serine, arginine, lysine and glutamic acid.
[0030] As an embodiment, the vulcanized rubber includes 2.5 to 20 parts of a vulcanization accelerator, and in a specific embodiment, it may be 2.5 to 3.5 parts.
[0031] As an embodiment, the vulcanization accelerator includes one or more of N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole and dibenzothiazole disulfide.
[0032] As an embodiment, the vulcanized rubber includes 0.05 to 5 parts of a functional additive, and in a specific embodiment, it can be 0.2 to 3 parts. As an embodiment, the functional additive includes one or more of serine, arginine, lysine and glutamic acid.
[0033] As one embodiment, the vulcanized rubber includes 0.2 to 3 parts of sulfur. As another embodiment, the vulcanized rubber includes 0.8 to 2 parts of sulfur. In a specific embodiment, it can be 1 to 1.5 parts.
[0034] As one embodiment, the vulcanized rubber includes 2 to 7 parts of zinc oxide. As another embodiment, the vulcanized rubber includes 4 to 6 parts of zinc oxide. In a specific example, it can be 5 parts.
[0035] As an embodiment, the vulcanized rubber includes 100 parts of deproteinized natural latex; the nitrogen content in the deproteinized natural latex is 0.02-0.2 wt.%, and in a specific embodiment, the nitrogen content can be 0.1 wt.%.
[0036] As an embodiment, the preparation of the deproteinized natural rubber latex comprises the following steps:
[0037] (1) mixing natural rubber latex, urea and a stabilizer, and sequentially standing and centrifuging the resulting mixed solution to obtain a pretreated natural rubber latex;
[0038] (2) diluting the pretreated natural rubber latex, mixing the obtained dilution with ammonia water and a stabilizer, and centrifuging again to obtain deproteinized natural rubber latex.
[0039] The invention mixes natural latex, urea and a stabilizer, and sequentially performs standing and centrifugation on the obtained mixed liquid to obtain the pretreated natural latex.
[0040] As an embodiment, the stabilizer is one or more of sodium dodecyl sulfate (SDS), sodium petroleum sulfonate, Tween and Paregal, the Tween is Tween-100, and the Paregal is Paregal O-20.
[0041] In a specific embodiment, the SDS is used in the form of an SDS solution, and the mass concentration of the SDS solution is 10%.
[0042] As an embodiment, the mass fraction of urea in the mixed solution is 0.05-0.2%, and in a specific embodiment, it can be 0.1%; as an embodiment, the mass fraction of the stabilizer in the mixed solution is 0.05-2%, and in a specific embodiment, it can be 0.25%.
[0043] As an embodiment, the standing is standing at room temperature for 0.5 to 4 hours, and in a specific embodiment, the standing is standing at room temperature for 1 hour. As an embodiment, in a specific embodiment, the centrifugal speed can be 7700 rpm.
[0044] The invention dilutes the pretreated natural latex, mixes the obtained dilution with ammonia water and a stabilizer, and then centrifuges again to obtain the deproteinized natural latex.
[0045] As an embodiment, the reagent used for dilution is water, and the volume of the diluent is twice the volume of the pretreated natural latex.
[0046] As an embodiment, the ammonia water is 0.1-0.7% of the mass of the diluent, and in a specific embodiment, the ammonia water is 0.5% of the mass of the diluent; as an embodiment, the stabilizer is 0.2-0.6% of the mass of the diluent, and in a specific embodiment, the stabilizer is 0.2% of the mass of the diluent.
[0047] As an embodiment, the rotation speed of the second centrifugation is 7700 rpm.
[0048] The present invention also provides a method for preparing the vulcanized rubber described in the above technical solution, comprising the following steps:
[0049] Mixing deproteinized natural rubber latex and functional additives to obtain modified deproteinized natural rubber latex;
[0050] The modified deproteinized natural rubber latex, the emulsion of the vulcanization accelerator, the emulsion of sulfur and the emulsion of zinc oxide are mixed, and the obtained mixture is molded and dried to obtain a mixed dry rubber;
[0051] The mixed dry rubber is kneaded and vulcanized in sequence to obtain the vulcanized rubber.
[0052] The invention mixes deproteinized natural rubber latex and functional additives to obtain modified deproteinized natural rubber latex.
[0053] As an embodiment, the functional additive is used in the form of a solution of the functional additive. As an embodiment, the mass concentration of the solution of the functional additive is 10-20%.
[0054] After obtaining the modified deproteinized natural rubber latex, the present invention mixes the modified deproteinized natural rubber latex, the emulsion of a vulcanization accelerator, the emulsion of sulfur and the emulsion of zinc oxide, and shapes and dries the obtained mixture to obtain a mixed dry rubber.
[0055] As an embodiment, the mass concentration of the vulcanization accelerator emulsion is 20-40%, and in a specific embodiment, it can be 30%; the mass concentration of the sulfur emulsion is 30-50%, and in a specific embodiment, it can be 40%; the mass concentration of the zinc oxide emulsion is 30-50%, and in a specific embodiment, it can be 40%.
[0056] As an embodiment, the mixing method is stirring, the stirring speed is 100-1000rpm, and the stirring time is 10-60min. In a specific embodiment, the stirring speed is 250rpm and the time is 30min. In a specific embodiment, the molding and drying is to spread the mixture on two glass plates and then dry it at room temperature.
[0057] After obtaining the mixed dry rubber, the present invention sequentially mixes and vulcanizes the mixed dry rubber to obtain the vulcanized rubber.
[0058] As an embodiment, the mixing is to mix the mixed dry rubber at 40-70° C. through a mixing roller for 20-60 times. In a specific embodiment, the mixing is to mix the mixed dry rubber at 40-70° C. through a mixing roller for 40 times. As an embodiment, the roller pitch of the mixing roller is 0.1-0.5 mm.
[0059] As an implementation mode, the vulcanization temperature is 140-180°C, the vulcanization pressure is 8-20MPa, and the vulcanization time is 10-50min. In a specific embodiment, the vulcanization temperature is 150°C, the vulcanization pressure is 15MPa, and the vulcanization time is 20min.
[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] Example 1
[0062] Urea and 10 wt% SDS solution were added to 15 kg of fresh natural latex, and the mixture was evenly mixed to obtain a mixed solution, in which the mass fraction of urea was 0.1% and the mass fraction of SDS was 0.25%.
[0063] The resulting mixed solution was allowed to stand at room temperature for 1 h, and then centrifuged on a disc centrifuge (rotation speed was 7700 rpm) to obtain a centrifuged sample;
[0064] The centrifuged sample was diluted to twice its original mass to obtain a dilution; ammonia water and 10 wt.% SDS solution were added to the dilution (the mass of the added ammonia water was 0.5% of the mass of the dilution, and the mass of the SDS was 0.2% of the mass of the dilution), and then centrifuged again to obtain deproteinized natural latex, recorded as UFNR.
[0065] Adding 20 wt.% serine solution to 100 parts by mass of UFNR and stirring for 10 minutes (wherein the mass fraction of serine in the serine solution is 0.75 parts relative to UFNR) to obtain modified UFNR;
[0066] The obtained modified UFNR was mixed with an emulsion containing 1.5 parts by mass of N-tert-butyl-2-benzothiazolesulfenamide (the mass concentration of N-tert-butyl-2-benzothiazolesulfenamide in the emulsion was 30%), an emulsion containing 1.5 parts by mass of sulfur (the mass concentration of sulfur in the emulsion was 40%), and an emulsion containing 5 parts of zinc oxide (the mass concentration of zinc oxide in the emulsion was 40%). After stirring for 30 minutes at a rotation speed of 250 rpm, the mixture was spread on two glass plates (large plate size: 24.5×15 cm, small plate size: 15×13 cm), and dried at room temperature to obtain a mixed dry glue.
[0067] The mixed dry rubber was rolled through a mixing roller (roller spacing of 0.2 mm) at 70° C. for 30 times, mixed, and then allowed to stand for 16 hours to obtain a mixed rubber;
[0068] The mixed rubber was subjected to the determination of the positive vulcanization time at a vulcanization temperature of 150°C using an MDR-2000E rotorless vulcanizer. The mixed rubber was then cut into rubber blocks of about 22 g and subjected to heating vulcanization using an XLB-D flat plate vulcanizer (vulcanization temperature of 150°C, time of 20 min, pressure of 15 MPa) to produce a 14×12 cm vulcanized rubber sheet (denoted as LS-0.75).
[0069] Example 2
[0070] The only difference from Example 1 is that the mass fraction of serine in the serine solution is 1.5 parts relative to UFNR, and the vulcanized rubber film is recorded as LS-1.5.
[0071] Example 3
[0072] The only difference from Example 1 is that the mass fraction of serine in the serine solution is 2.25 parts relative to UFNR, and the vulcanized rubber film is recorded as LS-2.25.
[0073] Example 4
[0074] The only difference from Example 1 is that the mass fraction of serine in the serine solution is 3 parts relative to UFNR, and the vulcanized rubber film is recorded as LS-3.
[0075] Example 5
[0076] The only difference from Example 1 is that the mass fraction of serine in the serine solution is 3.75 parts relative to UFNR, and the vulcanized rubber film is recorded as LS-3.75.
[0077] Example 6
[0078] Urea and 10 wt.% SDS solution were added to 15 kg of fresh natural latex, and the mixture was evenly mixed to obtain a mixed solution, in which the mass fraction of urea was 0.1% and the mass fraction of SDS was 0.25%.
[0079] The resulting mixed solution was allowed to stand at room temperature for 1 h, and then centrifuged on a disc centrifuge (rotation speed was 7700 rpm) to obtain a centrifuged sample;
[0080] The centrifuged sample was diluted to twice its original mass to obtain a dilution; ammonia water and 10 wt.% SDS solution were added to the dilution (the mass of the added ammonia water was 0.5% of the mass of the dilution, and the mass of the SDS was 0.2% of the mass of the dilution), and then centrifuged again to obtain deproteinized natural latex, recorded as UFNR.
[0081] Adding 12.9 wt.% arginine solution to 100 parts by mass of UFNR and stirring for 10 minutes (wherein the mass fraction of arginine in the arginine solution is 0.3 parts relative to UFNR) to obtain modified UFNR;
[0082] The obtained modified UFNR and an emulsion of 1.5 parts by mass of N-tert-butyl-2-benzothiazolesulfenamide (the mass concentration of N-tert-butyl-2-benzothiazolesulfenamide in the emulsion is 30%), an emulsion containing 1.5 parts by mass of sulfur (the mass concentration of sulfur in the emulsion is 40%) and an emulsion containing 5 parts of zinc oxide (the mass concentration of zinc oxide in the emulsion is 40%) were mixed, stirred at a rotation speed of 250 rpm for 30 minutes, and then spread on two glass plates (large plate size: 24.5×15 cm, small plate size: 15×13 cm), and dried at room temperature to obtain a mixed dry glue.
[0083] The mixed dry rubber was rolled through a mixing roller (roller spacing of 0.2 mm) at 70° C. for 30 times, mixed, and then allowed to stand for 16 hours to obtain a mixed rubber;
[0084] The mixed rubber was subjected to the determination of the positive vulcanization time at a vulcanization temperature of 150°C using an MDR-2000E rotorless vulcanizer. The mixed rubber was then cut into rubber blocks of about 22 g and subjected to heating vulcanization using an XLB-D flat plate vulcanizer (vulcanization temperature of 150°C, time of 20 min, pressure of 15 MPa) to produce a 14×12 cm vulcanized rubber sheet (denoted as A-0.3).
[0085] Example 7
[0086] The only difference from Example 1 is that the mass fraction of arginine in the arginine solution is 0.6 parts relative to UFNR, and the vulcanized rubber film is recorded as A-0.6.
[0087] Example 8
[0088] The only difference from Example 1 is that the mass fraction of arginine in the arginine solution is 0.9 parts relative to UFNR, and the vulcanized rubber film is recorded as A-0.9.
[0089] Example 9
[0090] The only difference from Example 1 is that the mass fraction of arginine in the arginine solution is 1.2 parts relative to UFNR, and the vulcanized rubber film is recorded as A-1.2.
[0091] Example 10
[0092] The only difference from Example 1 is that the mass fraction of arginine in the arginine solution is 1.5 parts relative to UFNR, and the vulcanized rubber film is recorded as A-1.5.
[0093] Comparative Example 1
[0094] Urea and 10 wt.% SDS solution were added to 15 kg of fresh natural latex, and the mixture was evenly mixed to obtain a mixed solution, in which the mass fraction of urea was 0.1% and the mass fraction of SDS was 0.25%.
[0095] The resulting mixed solution was allowed to stand at room temperature for 1 h, and then centrifuged on a disc centrifuge (rotation speed was 7700 rpm) to obtain a centrifuged sample;
[0096] The centrifuged sample was diluted to twice its original mass to obtain a dilution; ammonia water and 10 wt.% SDS solution were added to the dilution (the mass of the added ammonia water was 0.5% of the mass of the dilution, and the mass of the SDS was 0.2% of the mass of the dilution), and then centrifuged again to obtain deproteinized natural latex, recorded as UFNR.
[0097] The present invention performs a scanning electron microscope (SEM) test on UFNR and A-0.9 vulcanized natural rubber. The test steps are as follows: using liquid nitrogen to brittle the film, then putting it into an E-1045 ion sputtering instrument of Hitachi High-Tech Co., Ltd. to spray a metal film in a vacuum to eliminate the charging phenomenon, and then putting it into an S-4800 scanning electron microscope (SEM) of Hitachi High-Tech Co., Ltd. for testing, and performing elemental analysis on the sample by a Z230 Workstation energy dispersive X-ray spectrometer (EDS) of EDAX Company of the United States. Figure 1 The C, N, S, and Zn analysis elements of deproteinized vulcanized natural rubber UFNR under scanning electron microscopy and corresponding X-ray spectrum. Figure 2 The C, N, S, and Zn analysis elements of A-0.9 vulcanized natural rubber under scanning electron microscopy and corresponding X-ray spectrum are shown in Figure 2. Figures 1-2It can be seen that: by observing under a scanning electron microscope (SEM) at a magnification of 5K, there are a large number of particles aggregated in the deproteinized vulcanized natural rubber, and the size of these particles is significantly reduced after the addition of additives. This shows that the addition of arginine helps to disperse the vulcanized rubber additive particles. It can be found that most of the vulcanized rubber is composed of carbon and sulfur elements, and a small part is nitrogen and zinc elements. Nitrogen can be well dispersed in the vulcanized rubber. The sulfur element is first in a state of agglomeration, and is evenly dispersed after adding arginine, indicating that arginine can promote the dispersion of sulfur during the vulcanization process, and sulfur can better cross-link with the rubber molecular chain. The Zn element also has a similar dispersion in the rubber, indicating that the addition of functional additives improves the construction efficiency of sulfur and Zn elements in the rubber matrix network, reduces network defects, and thus improves the performance of vulcanized natural rubber.
[0098] test:
[0099] (1) Determination of mechanical properties
[0100] The samples were subjected to tensile testing at a rate of 500 mm / min using the AI-7000-SU1 electronic tensile testing machine produced by High Speed Rail Testing Instruments (Dongguan) Co., Ltd. in accordance with the GB / T528-2009 standard; the tear strength was measured at a rate of 500 mm / min in accordance with the GB / T529-2008 standard.
[0101] Table 1 Mechanical properties of deproteinized natural rubber and serine-added vulcanized natural rubber
[0102]
[0103] From Table 1, it can be seen that the addition of serine to vulcanized natural rubber has the highest tensile strength for LS-3.75 vulcanized rubber, and the tensile strength of other vulcanized rubbers with the addition of serine is better than that of deproteinized vulcanized natural rubber, and increases with the increase of serine content; while the addition of serine has little effect on the tear strength of natural rubber, and some individual properties have decreased. This may be due to the poor compatibility of serine in natural rubber, resulting in different actual amounts of serine added in natural rubber, and the mechanical properties of natural rubber will be different.
[0104] Table 2 Mechanical properties of deproteinized natural rubber and arginine-added vulcanized natural rubber
[0105]
[0106]
[0107] From Table 2, we can see that: (1) The tensile strength of the vulcanized rubber with 0.9 parts of arginine is the largest. After adding arginine, the tensile strength of the vulcanized rubber increases. With the increase of the nitrogen content of arginine, the tensile strength shows a trend of first increasing and then decreasing, increasing from 27.34MPa to 33.34MPa, an increase of 6MPa. (2) The 100% and 300% tensile stress of natural rubber are both improved, with the maximum increase of 0.12MPa and 0.23MPa respectively. (3) The elongation at break of the vulcanized rubber increased by up to 30%. (4) The tear strength has a similar trend to the tensile strength. With the increase of the nitrogen content of arginine, the tear strength of the vulcanized rubber first increases and then decreases, and is significantly higher than that of UFNR, with a maximum of 33.34kN / m. (5) After adding arginine, the tensile stress, tensile strength and tear strength of the vulcanized rubber are significantly improved. The comprehensive performance of natural rubber vulcanized rubber with 0.9 and 1.2 parts of arginine is the best.
[0108] Table 3 Aging properties and retention rate of deproteinized vulcanized natural rubber and serine-added vulcanized natural rubber
[0109]
[0110] It can be seen from Table 3 that after aging, the tensile strength, 100% modulus of elongation and 300% modulus of the vulcanized natural rubber with serine added are all improved, and increase with the increase of serine content, which are increased by 9.61MPa, 0.14MPa and 0.51MPa respectively.
[0111] The tensile strength retention rate of the vulcanized rubber increased except for the vulcanized rubber with 0.75 parts of serine added, and the LS-3.0 had the highest increase of 30.04%. The elongation retention rate of the vulcanized rubber with serine added was better than that of the deproteinized rubber, indicating that the aging performance of the rubber was improved. It can also be shown that the addition of serine has an anti-aging effect on natural rubber.
[0112] (2) Determination of aging properties of vulcanized rubber
[0113] Cut samples according to GB / T528-2009 standard. Use UA-2071A aging machine of Youken Technology Co., Ltd. to age the sample at 100℃ for 24h. After 1d, test the performance of the vulcanized rubber after hot air aging. Perform tensile test on the aged sample, the same as the mechanical property test method.
[0114] Table 4 Aging properties and retention rate of deproteinized vulcanized natural rubber and arginine-added vulcanized natural rubber
[0115]
[0116] As shown in Table 4, after aging, the tensile strength of the vulcanized rubber increases first and then decreases with the increase of arginine content. The tensile strength and tensile stress at break of the vulcanized rubber with 0.9 parts of arginine are the largest, increasing by 6.27MPa, 0.04MPa and 0.09MPa respectively, indicating that when 0.9 parts of arginine are added, the mechanical properties of the vulcanized rubber after aging are the best. The tensile strength, tensile stress at break, tensile strength retention rate and elongation at break retention rate are all higher than those of the deproteinized vulcanized rubber after adding arginine, indicating that the aging performance of the natural rubber with the addition of arginine is improved, indicating that arginine has an anti-aging effect in natural rubber.
[0117] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A vulcanized rubber, characterized in that: The raw materials for preparation include, by weight: The nitrogen content of the denitrogenated white natural rubber latex is 0.02 to 0.2 wt.%; The functional auxiliary agent includes one or more of serine, arginine, lysine and glutamic acid.
2. The vulcanized rubber according to claim 1, characterized in that The vulcanization accelerator includes one or more of N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole and dibenzothiazole disulfide.
3. The vulcanized rubber according to claim 1, characterized in that The preparation of the deproteinized natural rubber latex comprises the following steps: (1) mixing natural rubber latex, urea and a stabilizer, and sequentially standing and centrifuging the resulting mixed solution to obtain a pretreated natural rubber latex; (2) diluting the pretreated natural rubber latex, mixing the obtained dilution with ammonia water and a stabilizer, and centrifuging again to obtain deproteinized natural rubber latex.
4. The vulcanized rubber according to claim 3, characterized in that The stabilizer is one or more of sodium dodecyl sulfonate, sodium petroleum sulfonate, Tween and pyralidone.
5. The vulcanized rubber according to claim 3, characterized in that In step (2), the ammonia water accounts for 0.1 to 0.7% of the mass of the diluent.
6. The vulcanized rubber according to claim 3, characterized in that In step (2), the stabilizer is 0.2-0.6% of the mass of the diluent.
7. The method for preparing vulcanized rubber according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing deproteinized natural rubber latex and functional additives to obtain modified deproteinized natural rubber latex; The modified deproteinized natural rubber latex, the emulsion of the vulcanization accelerator, the emulsion of sulfur and the emulsion of zinc oxide are mixed, and the obtained mixture is molded and dried to obtain a mixed dry rubber; The mixed dry rubber is kneaded and vulcanized in sequence to obtain the vulcanized rubber.
8. The preparation method according to claim 7, characterized in that: The mixing method is stirring; the stirring speed is 100 to 1000 rpm, and the stirring time is 10 to 60 minutes.
9. The preparation method according to claim 7, characterized in that: The mixing is to mix the mixed dry rubber at 40-70° C. for 20-60 times through a mixing roller.
10. The preparation method according to claim 7, characterized in that: The vulcanization temperature is 140-180° C., the vulcanization pressure is 8-20 MPa, and the vulcanization time is 10-50 min.
Citation Information
Patent Citations
Method for improving oxygen aging resistance of protein-removed natural rubber
CN101851302A
Preparation method of low-protein natural latex
CN112010996A
Deproteinized natural rubber foaming product and preparation method thereof
CN118755139A
Low-protein natural rubber and method for preparation thereof
WO2022099883A1